The Horrors of the Body: Notes on Mikhail Bakhtin and the Images of the Grotesque Body - Gómez Ponce, Fernando Ariel (2022)
This article proposes an interpretation of the horror body as a historical prolongation of Bakhtinian grotesque. I pretend to demonstrate the relevance of the theory of Mikhail Bakhtin in order to study current manifestations where a material bodily principle collaborates with the description of periods of cultural mutations. In the historical transition from cinema to current TV series, the grotesque of body horror surfaces a bodily awareness that reveals our biological and cultural fears, many of which are linked to certain postmodern transformations.